TOTAL FLAVONOID DAN AKTIVITAS ANTIBAKTERI INFUSA DAUN SEMPUR (Dillenia suffruticosa (Griff. Ex Hook f. & Thomson) Martelli - Syafriana, Vilya; Indriyani, Indriyani; Puspitasari, Lia (BRIN Publishing (Penerbit BRIN), 2024)
Sempur leaf (Dillenia suffruticosa) is a traditional medicine plant that contains flavonoids and is thought to be effective in treating gastrointestinal symptoms such as diarrhea. This research aims to evaluate the total flavonoid content of a sempur leaf infusion and assess its antibacterial effectiveness against two bacteria that cause gastroenteritis, namely Escherichia coli and Salmonella typhi. The infusion was carried out by heating the simplicial in distilled water for 15 minutes at 90 0C. The total flavonoid content was determined using UV-Vis Spectrophotometer with quercetin as the standard. Meanwhile, antibacterial activity was measured using the disc diffusion method with Ciprofloxacin as a positive control and distilled water as a negative control. The total flavonoid content of sempur leaf infusion was about 8.803 ± 0.6990 mgQE/g. In contrast, this sempur leaf infusion demonstrated no antibacterial activity against E. coli or S. typhi.